Improving the adhesion, flexibility, and hemostatic efficacy of a sprayable polymer blend surgical sealant by incorporating silica particles. (May 2019) - Daristotle, John L.; Zaki, Shadden T.; Lau, Lung W.; Torres, Leopoldo; Zografos, Aristotelis; Srinivasan, Priya; Ayyub, Omar B.; Sandler, Anthony D.; Kofinas, Peter
Graphical abstract: Abstract: Commercially available surgical sealants for internal use either lack sufficient adhesion or produce cytotoxicity. This work describes a surgical sealant based on a polymer blend of poly(lactic-co-glycolic acid) (PLGA) and poly(ethylene glycol) (PEG) that increases wet tissue adherence by incorporation of nano-to-microscale silica particles, without significantly affecting cell viability, biodegradation rate, or local inflammation. In functional studies, PLGA/PEG/silica composite sealants produce intestinal burst pressures that are comparable to cyanoacrylate glue (160 mmHg), ∼2 times greater than the non-composite sealant (59 mmHg), and ∼3 times greater than fibrin glue (49 mmHg). The addition of silica to PLGA/PEG is compatible with a sprayable in situ deposition method called solution blow spinning and decreases coagulation time in vitro and in vivo. These improvements are biocompatible and cause minimal additional inflammation, demonstrating the potential of a simple composite design to increase adhesion to wet tissue through physical, noncovalent mechanisms and enable use in procedures requiring simultaneous occlusion and hemostasis. Statement of Significance: Incorporating silica particles increases the tissue adhesion of a polymer blend surgical sealant. The particles enable interfacial physical bonding with tissue and enhance the flexibility of the bulk of the sealant, without significantly affecting cytotoxicity, inflammation, or biodegradation. These studies also demonstrate how silica particles decrease blood coagulation time. This surgical sealant improves upon conventional devices because it can be easily deposited with accuracy directly onto the surgical site as a solid polymer fiber mat. The deposition method, solution blow spinning, allows for high loading in the composite fibers, which are sprayed from a polymer blend solution containing suspended silica particles. These findings could easily be translated to other implantable or wearable devices due to the versatility of silica particles.